Vulnerability and inclusion in the control of acute respiratory infections policy in Namibia (Journal for Studies in Humanities and Social Sciences, 2017)
This paper presents the findings on a policy analysis of the Control of Acute and Respiratory Infections (ARIs) of the Ministry of Health and Social Services in Namibia. The policy document was analysed against 21 core concepts of access to health and its effectiveness in 12 vulnerable groups using the EquiFrame, a novel analytical and peer reviewed framework that serves to identify the strengths and weaknesses in current health policies with regard to the degree in which a policy promotes and protects the core concepts and vulnerable groups in society (Mannan et al. (2013, p. 2). The 2006/07 Namibia Demographic and Health Survey (NDHS) reported that close to four percent of children under five years of age show symptoms of ARI in the two weeks preceding the survey, while 17 percent of children under five have been reported as having fever, a major sign of malaria, which contributes to high levels of malnutrition and death in children (NDHS 2006/2007). In 1995, the Ministry of Health and Social Services in Namibia devised a policy programme to reduce ARI mortality by 30%, the incidence by 15%, and the rate of complication by 20% in children under five. EquiFrame was used to analyse the Control of ARI Programme and a data extraction matrix was used to record its quality. EquiFrame was also used to determine the extent to which the ARI policy document would address issues of vulnerability and inclusion in health provision. The overall ranking of the programme showed it to be of low quality, necessitating a revision so that vulnerability and social inclusion components could be adequately ad-dressed.